Archaeological theory in the new millennium : introducing current perspectives - Harris, Oliver J.T.; Cipolla, Craig N., 1978- (London ; New York : Routledge, Taylor & Francis Group, 2017)
"Provides an accessible account of the changing world of archaeological theory. It charts the emergence of the new emphasis on relations as well as engaging with current theoretical trends and the thinkers archaeologists regularly employ. This book will be an essential guide to cutting-edge theory for students and for professionals wishing to reacquaint themselves with this field. Oliver J.T. Harris is lecturer in archaeology in the School of Archaeology & Ancient History, University of Leicester. Craig N. Cipolla is lecturer in historical archaeology in the School of Archaeology & Ancient History, University of Leicester"--Provided by publisher.
An introduction to contemporary archaeological theory : confronting dualisms -- Beyond paradigms : a potted history of archaeological thought -- Between thoughts and things : theorising practice and agency -- Situating things in society : identity and personhood -- Secret lives of things : object agency and biography -- Things make people? : considering materiality, phenomenology, experience and entanglement -- Mediating the world : archaeological semiotics -- Finding symmetry : actor-network-theory and new materialism -- Multi-species archaeology : people, plants and animals -- "Others" : postcolonialism, the ontological turn and colonised things -- On breaking walls and building relations : a conclusion.
Includes bibliographical references (pages 216-234) and index.
Keywords: Archaeology -- Philosophy; Archaeology -- Social aspects; Social change